Methodological Support for the Development of Strategies for the Socio-Economic Development of Municipalities in Russia - M. Yu. Elsukov; N. N. Kirillova (Управленческое консультирование)
The article presents the results of an analysis of methodological support for the preparation of strategies for the socio-economic development of municipalities. At the beginning of 2024, methodological recommendations have been developed in 24 regions of the Russian Federation. They were compared in terms of the degree of consistency with strategic documents at the federal and regional levels, the presence of common development principles, the need to involve stakeholders in the planning process and the organization of public hearings. Despite the variety of approaches to the structure, content, and emphasis on certain organizational aspects, it can be said that methodological support for the process of strategic planning of municipalities by regional levels of government is for the most part of a formal nature, ignoring real resource opportunities and problems their constituent territories.